Floral phase and sucrose/boric acid concentrations on in vitro germination of Inga edulis (Mart.), pollen grain - Santos, Ana Claudia Schllemer dos; Castro, Juliana Dias de; Bressan, Daiane; Júnior, Américo Wagner; Guollo, Karina (Scientia Agraria Paranaensis, 2018)
The aim of this work was to determine the ideal stage of pollen collection and the best concentrations of sucrose and boric acid in the culture medium for the in vitro germination of inga fruit tree pollen. For this, the work was carried out in two stages, one using concentrations of sucrose in the culture medium (0, 5, 10, 20 and 30%) - experiment 1. Another one using the best sucrose concentration, with concentrations (0, 100, 200 and 300 mg L-1) - experiment 2. In the two experiments, two flowering phases were use: pre-anthesis and post-anthesis. For both experiments, the culture medium contained 1% agar to solidify the medium and all treatments remained in BOD for 24 h at a temperature controlled at 25°C. For the experiment 1 with sucrose, DIC was use in factorial 2 x 5, with 4 replicates, and for the experiment 2 with boric acid, DIC was use in factorial 2 x 4, with 4 replicates. Data were submit to analysis of variance and regression. For pollen grains obtained from pre-anthesis, the maximum technical efficiency point (PMET) was obtain with 11% sucrose added to the culture medium, thus achieving 33% germination. As for pollen grains obtained from flowers in post-anthesis, PMET was reach with 8% of sucrose in the culture medium, obtaining 32% of germination. Within the concentrations evaluated in the experiment, boric acid did not promote increase of in vitro germination of pollen from inga fruit tree.